Observation and Simulation of Near-Surface Wind and Its Variation with Topography in Urumqi, West China - 金莉莉 李振杰 何清 缪启龙 张虎强 杨兴华 (Acta meteorologica Sinica, 2016)
Near-surface wind measurements obtained with five 100-m meteorology towers, 39 regional automatic stations, and simulations by the Weather Research and Forecasting （WRF） model were used to investigate the spatial structure of topography-driven flows in the complex urban terrain of Urumqi, China. The results showed that the wind directions were mainly northerly and southerly within the reach of 100 m above ground in the southern suburbs, urban area, and northern suburbs, which were consistent with the form of the Urumqi gorge. Strong winds were observed in southern suburbs, whereas the winds in the urban, northern suburbs, and northern rural areas were weak. Static wind occurred more frequently in the urban and northern rural areas than in the southern suburbs. In the southern suburbs, wind speed was relatively high throughout the year and did not show significant seasonal variations. The average annual wind speed in this region varied among 1.9-5.5, 1.1-3.6, 1.2 4.3, 1.2 4.3, and 1.1 3.5 m s-1 within the reach of 100 m above ground at Yannanlijiao, Shuitashan, Liyushan, Hongguangshan, and Midong, respectively. The flow characteristics comprised more airflows around the mountain, where the convergence and divergence were dominated by the terrain in eastern and southwestern Urumqi. Further analysis showed that there was a significant mountain-valley wind in spring, summer, and autumn, which occurred more frequently in spring and summer for 10- 11 h in urban and northern suburbs. During daytime, there was a northerly valley wind, whereas at night there was a southerly mountain wind. The conversion time from the mountain wind to the valley wind was during 0800-1000 LST （Local Standard Time）, while the conversion from the valley wind to the mountain wind was during 1900- 2100 LST. The influence of the mountain-valley wind in Urumqi City was most obvious at 850 hPa, according to the WRF model.